A Note on Unoccupied Houses - Robinson, H. W. (Review of Economic Studies, 1939)
Journal Article A Note on Unoccupied Houses Get access H. W. Robinson H. W. Robinson Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 3, June 1939, Pages 209–214, https://doi.org/10.2307/2967646 Published: 01 June 1939